Genome-wide identification of the E-class gene family in wheat: evolution, expression, and interaction - Bai, Xionghui; Qiao, Pengfei; Liu, Hanxiao; Shang, Yuping; Guo, Jie; Dai, Keli (Frontiers in Plant Science, 2024)
Wheat (Triticum aestivum L.) is among the most important crop worldwide. Given a growing population and changing climate, enhancing wheat yield is of great importance. Yield is closely associated with flower and spike development, and Eclass genes play important roles in the flower and kernel development of plants.Currently, the absence of systematic analysis on the E gene family hinders our comprehension of their roles in plant growth and development. Thus, this study aims to analyze the E gene family in wheat to understand their roles in flower and kernel development, crucial for enhancing wheat yield. Based on a homology comparison, Fifteen E-class genes (TaEs) were identified in common wheat. Nine E-class genes were detected in five ancestral/closely related species, including one in Aegilops tauschii (AtE), one in T. urartu (TuEs), two in T. turgidum (TtEs), two in T. dicoccoides (TdEs), and three in T. spelta (TsEs). The 24 E-class genes were classified into three subgroups using a phylogenetic approach. All genes were highly expressed in spikes, and most were only highly expressed at the floret meristem stage. The effects of TaSEP5-A on flowering and growth cycles were confirmed in homologous mutants and transgenic Arabidopsis thaliana. The E-class genes were able to regulate the growth cycle of Arabidopsis. Finally, we confirmed the interactions between TaSEP5-A and other wheat E-class genes based on yeast two-hybrid assays.Collectively, our findings provide information regarding the E-class genes in wheat and will potentially promote the application of these genes in wheat improvement.